RELOCATING THE STREET VENDORS TO PANTAI TAK BEROMBAK (PTB) AS STRATEGY OF MAROS GOVERNMENT - Mustafa Mustafa; Zainal Abidin; Sarnawiah Sarnawiah (Salewangang Institut Publishing, 2018)
The ´growth of cities in Indonesia cannot be separated from the informal sector presence which has been integrated to every urban life activity. The existence of Street Vendors sometimes create its own problems such as urban planning which is chaotic. The long-term goal of this research is to find out the strategy of Maros Government in relocating Sales Vendors, to make an improvement overview of Street Vendors income before and after relocation, to formulate appropriate policies and relocation programs. While the specific targets to be achieved in this research is that it is necessary to identify the right strategy in refuting the income of street vendors without decrease the income. The purpose of traders’ relocation is in order to avoid jobless and encourage the economic growth faced by the Government of Maros that necessary to improve strategies in increasing the income of sales vendors (PKL) .The data collection techniques are observation, survey and interview. The method used to achieve the objectives is qualitative descriptive research. The result of this research is to approach the government's strategy for the street vendors to be relocated and also socialize aneffective way so that they welcome to move, and provide supporting facilities for the community to visit the Pantai Tak Berombak.